A Neuroetholical Study of Human Behavior in the Context of Meditation in Religions - Hubert Jurjewicz (Communications - Scientific letters of the University of Zilina, 2017)
A neuroethological examination of the behavior and the cognition of nonhuman and human beings shows a connection between biological specializations to social behavior. It shows that ancestral organs and manners are usually regulated differently, duplicated, and repurposed so that an animal can act in a particular way. A neuroethological approach shows that highly specialized mechanisms have changed over time to translate immediate parallel circuits and social contexts that have changed over time. According to this approach, highly specialized mechanisms have changed to enable translation of perceived nonsocial and social signals into partially interconnected nonsocial and shared motivational pointers that have together created general-purpose techniques that command behavior. Dissimilarities in social conduct between species and between members of a species are partly due to neuromodulatory regulation of neutral circuits that appears to be controlled partly by genetics. The intraspecific difference in social behavior is important as it assists an animal to adapt to a particular situation. This review suggests that neuroethological approach to human behavior can assist in the understanding of human behavior.